Environmental permit in the pandemic time of Covid-19. Issue 1 (October 2021) - Triwibowo, Prastiyo; Syahrin, Alvi; Suhaidi; Sirait, Ningrum Natasya
Abstract: During the COVID-19 pandemic, the role of all state officials and the public is urgently needed in preventing pollution and environmental damage. One of the instruments in an effort to prevent environmental pollution and damage is an environmental permit, as stipulated in Article 1 number 35 Law Number 32 of 2009 concerning Environmental Protection and Management which is further regulated in Government Regulation Number 27 of 2012 concerning Environmental Permits. With the existence of this Law, it is mandatory for business actors who are obliged to do EIA and UKL-UPL must also have an environmental permit. The enactment of environmental permits in accordance with Government Regulation Number 27 of 2012 equates environmental documents as environmental permits. As one of the problems in this research is how the legal arrangements for business actors and / or activities related to environmental permits. The research method used in this thesis is normative juridical research. This research was conducted to examine previous studies on legal principles regarding criminal charges related to environmental permits. Based on the description above, it can be concluded that the legal arrangements related to environmental permits are contained in Article 1 number 35 UUPPLH and Article 1 PP. No. 27 of 2012 concerning Environmental Permits is a permit that is given to every person who carries out a business and / or mandatory Amdal or UKL-UPL activities in the framework of environmental protection and management as a prerequisite for obtaining a business and / or activity license